Community Development through Bebegig Sukamantri-Themed Souvenir Production for Strengthening Intangible Cultural Heritage and the Creative Economy in Indonesia - Edi Setiadi Putra; Muhammad Djalu Djatmiko; Iyus Kusnaedi; Ardhiana Muksin Machdi; Abimanyu Al Farisi; Muhammad Rachmat Sarodji; Rizki Muhammad Nurdin (International Journal Of Community Service, 2026)
The sustainability of Bebegig Sukamantri, an Intangible Cultural Heritage (ICH) of Ciamis Regency, faces significant challenges due to limited community participation in the development of culture-based tourism souvenirs. This condition has hindered the utilization of Bebegig as both a cultural identity and a source of creative economic development. The 2026 Nusantara Arts Innovation Program (PISN) was designed to enhance community capacity through training in the design and production of souvenirs inspired by Bebegig Sukamantri. The program employed a Community Development approach, positioning Sanggar Seni Bebegig Sukamantri Baladdewa as both a partner and the principal actor throughout all stages of implementation. The training integrated Sundanese cultural knowledge, traditional woodcarving techniques, silicone mold-making, and resin casting for souvenir production. The results demonstrated a significant improvement in community capacity. The training successfully improved technical skills by 100% across 20 participants and generated 12 new prototype souvenir designs, benefiting entrepreneurs from several villages in Sukamantri District. The program confirms that a community-based empowerment approach is effective in strengthening the preservation of Intangible Cultural Heritage while simultaneously promoting the creative economy through an adaptive and replicable training model.